The INSPIRE Framework: How Public Administrators Can Increase Compliance with Written Requests Using Behavioral Techniques. (8th November 2018) - Faulkner, Nicholas; Borg, Kim; Bragge, Peter; Curtis, Jim; Ghafoori, Eraj; Goodwin, Denise; Jorgensen, Bradley S.; Jungbluth, Lena; Kneebone, Sarah; Smith, Liam; Wright, Breanna; Wright, Paula
Abstract: Public administrators rely on written communications to send information to citizens and stakeholders, and they are among the heaviest users of the postal service. Behavioral science research has identified several techniques that public administrators can use to increase compliance with written requests and, in turn, increase effectiveness. Currently, however, many written communications from government bodies are not written in a manner that utilizes these techniques. It remains an ongoing challenge for public administrators to identify, understand, and use these techniques in the written communications sent by their organizations. This article presents a framework capturing seven prominent techniques in a simple mnemonic—INSPIRE—that is already being used by several government bodies in Australia. It also provides practical examples of how to use each technique and demonstrates that using these techniques could result in large aggregate improvements in effectiveness and socially desirable outcomes of public administrators' written communications .